Sisymbrium officinale, the Plant of Singers: A Review of Its Properties and Uses - Zorzan, Maira; Zucca, Paolo; Collazuol, Daniela; Peddio, Stefania; Rescigno, Antonio; Pezzani, Raffaele (Planta Medica, 2020)
Sisymbrium officinale (hedge mustard and formerly called Erysimum officinale) is a common plant in wild lands of Europe and Africa. It is also cultivated for its seeds and leaves to be used in salad or mustard. Sisymbrium officinale is useful not only in culinary preparations, but it also seems to possess interesting therapeutic properties, especially for throat diseases such as aphonia and hoarseness. For this reason, it is commonly called “herb of singers” (in Italian, “Erba dei cantanti”). Indeed a cup of Sisymbrium officinale infusion is frequently consumed by singers before artistic performance, even if its beneficial ability still needs to be scientifically demonstrated. Some preliminary data can be analyzed, but new efforts and resources should be devoted to study and investigate a plant with valuable therapeutic potential. This review summarizes the data available for Sisymbrium officinale.
Keywords: Sisymbrium officinale; Erysimum officinale; hedge mustard; Erba dei cantanti; Hierba de los cantores; Brassicaceae